Cationic polycyclization of ynamides: building up molecular complexity. Issue 20 (9th May 2017) - Theunissen, Cédric; Métayer, Benoît; Lecomte, Morgan; Henry, Nicolas; Chan, Hwai-Chien; Compain, Guillaume; Gérard, Phidéline; Bachmann, Christian; Mokhtari, Naima; Marrot, Jérome; Martin-Mingot, Agnès; Thibaudeau, Sébastien; et al.
Abstract : Simple activation of readily available ynamides under acidic conditions triggers an unprecedented cationic polycyclization yielding highly substituted polycyclic nitrogen heterocycles. Abstract : Polycyclization reactions are among the most efficient synthetic tools for the synthesis of complex, polycyclic molecules in a single operation from simple starting materials. We report in this manuscript a full account on the discovery and development of a novel cationic polycyclization from readily available ynamides. Simple activation of these building blocks under acidic conditions enables the generation of highly reactive activated keteniminium ions, which triggers an unprecedented cationic polycyclization yielding highly substituted polycyclic nitrogen heterocycles possessing up to seven fused cycles and three contiguous stereocenters.